Shared Flow and Positive Collective Gatherings [Flujo Compartido y Reuniones Colectivas Positivas] - Wlodarczyk, A (Universidad de Murcia Servicio de Publicaciones, 2016)
Collective gatherings or rituals promote optimal experiences in socially acceptable circumstances. Few studies have empirically examined the experience of flow shared by a group in collective situations. The present research examined the multi-dimensional structure of shared flow experience and its role in explaining positive effects of participation in collective ritualized gatherings on personal wellbeing and social cohesion. In this longitudinal study (N = 550) participants of a local festival celebrated in San Sebastian (Tamborrada) responded to an online questionnaire at three different times. Confirmatory factor analyses supported a structure composed of nine first-order factors and one second-order factor with a 27-item version of the scale. Further, structural equation modeling analyses controlling for the pre-event scores showed indirect effects of participation in Tamborrada through shared flow on happiness, collective efficacy, identity fusion, and social integration. This research concludes that positive collective gatherings stimulate shared flow experiences and thus promote personal wellbeing and social cohesion. We discuss both the implications of these results and the utility of the Shared Flow Scale in positive psychology research. © 2016: Servicio de Publicaciones de la Universidad de Murcia.
Keywords: shared flow; collective gatherings; positive psychology; wellbeing; collective efficacy; identity fusion